Pengaruh Layanan Konseling Kelompok dengan Pendekatan Behavior Terhadap Perilaku Bullying Siswa Kelas VIII di SMP N 1 Demak - Khafidhiyah, Khusnul; Fitriana, Siti; Venty, Venty (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
This study aims to determine the effect of group counseling services with a behavior approach on bullying behavior of class VIII students at Demak 1 Public Middle School. This type of research is quantitative. The research method used in this study was a pre-experimental design with a one group pretest posttest research design. The population of this research is the research population of 313 students. The sample taken was class VIII B, which consisted of 32 students using purposive sampling technique. The data in this study were obtained through a psychological scale. Abnormal data using the Wilcoxon test is significant (2-tailed) of 0.005. From the basis of the decision in the calculation of the Wilcoxon test, the sig. 0.005 <0.05 which means that the proposed hypothesis is